Image Tactics in Public Speeches of the Head of the Reg - A. V. Chepkasov (Kemerovo State University, 2021)
The article features the way political discourse shapes the image of the region. The research was based on a number of speeches given by A. G. Tuleyev, the ex-governor of the Kemerovo Region. The author used the classification of communicative strategies and tactics developed by O. S. Issers. The strategies demonstrated a strong suggestive potential aimed at changing the values and worldview of the recipient while promoting the image of the territory and its main political figure. The speeches appeared to be quite expressive as they contained a lot of emotional vocabulary, which was almost completely absent from the original written texts. A. G. Tuleyev chose informative and incentive tactics, e.g. focus on the positive development of the region (22 %), campaigning tactics (15 %), and historical references (12 %). The ex-governor pursued several parallel goals, e.g. to describe the region as dynamic, attractive, and prosperous while demonstrating his care about the electorate and showing respect to people of hard labor.